Comparing Questionnaire and Verbal Guise Technique : Mainland Chinese Attitudes towards English varieties - Shengnan, Li; Ting, Su Hie (Ambarrukmo Tourism Institute (STIPRAM) Yogyakarta, Indonesia, 2022)
In the field of sociolinguistics, little is known about the consistency of direct and indirect measures of language attitudes. This study examined explicit and implicit attitudes of Chinese undergraduates toward British English, American English, Hong Kong English and China English. Questionnaires were employed as a direct method and verbal-guise technique (VGT) as an indirect method to study the language attitudes of students from a private university in Shandong Province, China. The questionnaire data were from 110 participants, and the VGT data were from 96 participants who listened to recordings of the four English varieties, and evaluated the speakers on 16 traits representing the dimensions of status and solidarity. Their attitudes were marginally positive on both direct and indirect measures. The questionnaire results showed mean scores between 3.57 (American English) and 4.48 (China English) on a scale of six for the four English varieties. The VGT results showed mean scores between 3.64 (American English) and 4.01 (British English). British English was ranked slightly higher than American English in both measures. The implicit attitudes towards Hong Kong English were slightly more positive than China English, but explicit attitudes showed an opposite pattern. However, t-tests showed that there were no significant differences between the Chinese undergraduates’ explicit and implicit attitudes towards the four varieties of English. The findings suggest that language attitude can be reliably measured using either questionnaires or VGT.